THE GOLDEN PERIOD OF THE UMAYYAD DYNASTY: PROGRESSIVE ECONOMIC ELABORATION DURING THE REIGN OF UMAR BIN ABDUL AZIZ - Johan Septian Putra; Nofrisyah, Sirvi; Karali, Nurcan (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2025)
The Umayyad Dynasty was considered an advanced and developed state because the welfare of its people was well achieved, partly through economic progress and development. A positive impression is associated with the governance of Caliph Umar bin Abdul Aziz, the supreme leader of the Umayyad Dynasty. Although his reign was brief, he had a significant impact on the economic progress of the state, which in turn influenced the prosperity and well-being of society. This makes his policies and key economic development initiatives an interesting subject for study. This article employs historical research methods, which include four stages: heuristics (source collection), source criticism (internal and external evaluation), interpretation (data classification and causal analysis), and explanation in the form of historiography. The findings of this study highlight that Caliph Umar bin Abdul Aziz was one of the greatest leaders in Islamic history, known for his justice, wisdom, and commitment to Islamic values. He was also known for his simplicity, rejecting personal wealth from his position of power, and viewing the caliphate as a means to serve the people rather than enrich himself or his family. Upholding justice and tolerance, Umar bin Abdul Aziz treated his people fairly, regardless of religion, ethnicity, or social status, and ensured the protection of non-Muslim rights within his territory.